Tunable photoluminescence and energy transfer of Eu3+,Ho3+-doped Ca0.05Y1.93-xO2 nanophosphors for warm white LEDs applications - Dwivedi, Arpita; Srivastava, Monika; Srivastava, Amit; Upadhyay, Chandan; Srivastava, Sanjay Kumar (Nature Research, 2022)
A series of Eu3+ ions doped Ca0.05Y1.93-xO3:0.02Ho3+ (CYO:Ho3+,xEu3+) nanophosphors having multicolour tuneability have been synthesised by following a simplistic solution combustion approach. The synthesised samples have been characterised by employing X-ray diffraction (XRD), Transmission electron microscope (TEM), and Fourier transforms infrared spectroscopy (FTIR). The optical properties have been engrossed by UV–visible and photoluminescent excitation and emission spectra, and decay lifetimes measurements. The characteristic emission, which occurs due to the f-f transition of Ho3+ and Eu3+ has been observed in emission spectra with excitation of 448 nm. By adjusting the doping ratio of Ho3+/Eu3+, the as-synthesized nanophosphor accomplishes multicolour tunability from green-yellow to red. Emission spectra and decay lifetime curve recommend dipole–dipole interaction causes energy transfer from Ho3+ → Eu3+. The energy transfer process from Ho3+ to Eu3+ has been confirmed through electric dipole–dipole interaction with critical distance 15.146 Å. Moreover, temperature dependent emission spectra show the high thermal stability with an activation energy ⁓ 0.21 eV, with the quantum efficiency of 83.6%. CIE coordinate illustrates that the singly doped Ho3+ and Eu3+ lie in the green and red region, respectively, while the as-synthesized CYO:Ho3+,xEu3+shows tunability from green to red with low CCT and high colour purity values. Hence, the CYO:Ho3+,xEu3+nanophosphor may be a near-UV excited multicolour colour-tunable pertinent candidate with potential prospects for multicolour- display and near-ultraviolet lighting applications.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Tunable; nanophosphors; white LEDs